Spinocerebellar Ataxia: The Role of Optometry and Binocular Vision Therapy in Rehabilitation and Improving Quality of life. - Mishra, Ankita; Sharma, Preeti; Singh, Prem Kumar; Tibrewal, Shailja; Ganesh, Suma (Optometry & Visual Performance, 2026)
Background: Spinocerebellar ataxia (SCA) is a group of progressive, inherited neurodegenerative disorders that impact coordination, balance, and vision. SCA subtypes, especially SCA7, present unique ocular manifestations, such as reduced visual acuity, color vision deficits, retinal degeneration, and oculomotor dysfunction. This multidisciplinary care approach enables patients to live more confidently and independently despite the visual and neurological challenges posed by SCA. Case Report: A 65-year-old male with spinocerebellar ataxia type 3 (SCA3) presented with diplopia, primarily at distance, and limitations in extraocular movements. Clinical evaluation revealed esotropia at distance and intermittent exotropia at near, managed effectively with 3Δ base-out correction and binocular vision therapy including vergence exercises. Despite underlying neurodegenerative pathology and coexisting hyperthyroidism, the patient achieved significant symptomatic relief and visual comfort over two years. Conclusion: This case highlights the role of nonsurgical, tailored optometric intervention in managing complex diplopia cases associated with neurological conditions.